Kajian terhadap kesedaran pekerja di lima tapak pembinaan di Daerah Seberang Perai Tengah, Pulau Pinang terhadap keselamatan dan kesihatan pekerjaan di tempat kerja - Muhamad Shukrey, Sharif (2015)
The purpose of this study is to determine the level of awareness among workers at construction workers in District of Seberang Perai Tengah towards occupational safety and health at the workplace. Questioneaire were used as the main instrument for obtaining data for this study. The data was analyzed descriptively based on frequency, percentage and mean in order to determine the level of awareness of the respondent towards occupational safety and health at workplace. Surveyed been focused for five Construction Sit in District of Seberang Perai Tengah Pulau Pinang. To examine the relationship between demographic factors and respondents' awareness towards occupational safety and health at tha workplace., the Pearson Correlation was used.The results showed that workers in District of Seberang Perai Tengah had a high level of awareness of occupational safety and health at workplace based on their overall mean score 4.15. Findings also showed that demographic factors did not influence the level of awareness, whether directly or indirectly. The factors that were analysed recorded a level of relationship of <0.20 and 0.20-0.40 only. This indicates a weak correlation